2018
DOI: 10.1111/febs.14620
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for prolidase deficiency disease mechanisms

Abstract: All refined structure coordinates as well as the corresponding structure factor amplitudes have been deposited in the PDB under the accession numbers 5MBY, 5MBZ, 5MC0, 5MC1, 5MC2, 5MC3, 5MC4, 5MC5, 6H2P, 6H2Q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Several studies showed the potential increase in total prolidase activity in cultured fibroblasts [41][42][43][44] and various therapeutic therapies were investigated [9,[45][46][47][48][49][50][51], but to date no efficient treatment was introduced. In recent years, we have structurally characterized wt prolidase [25] and a series of eight single amino acid substitution or deletions [10] and we could show that one of the major causes of loss of function (LOF) was structural destabilization induced by bulky side chains introduced in places of small ones. Previously, Besio et al showed that the induction of the chaperonins Hsp90 and Hsp70 in cultured fibroblasts derived from patients leads to partial rescue of prolidase activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies showed the potential increase in total prolidase activity in cultured fibroblasts [41][42][43][44] and various therapeutic therapies were investigated [9,[45][46][47][48][49][50][51], but to date no efficient treatment was introduced. In recent years, we have structurally characterized wt prolidase [25] and a series of eight single amino acid substitution or deletions [10] and we could show that one of the major causes of loss of function (LOF) was structural destabilization induced by bulky side chains introduced in places of small ones. Previously, Besio et al showed that the induction of the chaperonins Hsp90 and Hsp70 in cultured fibroblasts derived from patients leads to partial rescue of prolidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…A single peak corresponding to prolidase was collected, concentrated to~50 mgÁmL À1 , and used for crystallization trials or aliquoted and flash-frozen in liquid nitrogen (LN 2 ) for later use. Prolidase expression in Rosetta (DE3) cells followed the same procedure and was previously described [10,25].…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 3 more Smart Citations